Management of growth disorders - Aman Bhakti Pulungan; Henriette A. Delemarre vande Waal (Paediatrica Indonesiana, 2002)
Growth is the most fundamental characteristic of childhood. As multi factorial and complex as growing process, children normally grow in a remarkably predictable manner. Deviation from this normal pattern of growth can be the first manifestation of diseases. Both endocrine and nonendocrine disorders may occur and involve any organ system of the body. Frequent and accurate assessment of growth therefore is of primary importance for physicians and nurses caring for children.1